FOREVER CRISIS adaptive global governance for an era of accelerating complexity. - Day, Adam. ([S.l.] : ROUTLEDGE, 2024)
This book is an introduction to complex systems thinking at the global governance level. It offers concepts, tools, and ways of thinking about how systems change that can be applied to the most wicked problems facing the world today. More than an abstract argument for complexity theory, the book offers a targeted critique of today's highest-profile proposals for improving the governance of our environment, security, finance, health, and digital space. It suggests that we should spend less effort and resources on upgrading existing institutions, and more on understanding how they (and we) relate to each other. The volume will be essential reading for public policymakers, NGOs and think tanks, foreign policy experts, government officials, and global decision-makers.
Keywords: International cooperation; International relations; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Public Policy / General; POLITICAL SCIENCE / Government / International